Perceptions of Life Insurance Among Young Professionals in Higher Education - Osit, Ansherina (Journal of Interdisciplinary Perspectives, 2026)
Life insurance plays an important role in helping individuals prepare for financial uncertainties, particularly among young professionals who are in the early stages of building financial stability. This study examined the level of awareness, perceived barriers, and motivating factors influencing life insurance adoption among young university professionals, specifically non-teaching professionals at the University of Baguio. Employing a descriptive-correlational research design, data were collected using a validated structured questionnaire administered to 126 eligible employees; 98 respondents completed the survey. Findings revealed a high level of awareness and generally positive perceptions of life insurance, although actual policy ownership remained moderate. Perceived barriers were low overall, with financial concerns identified as the only moderate barrier. In contrast, motivating factors such as family security, financial preparedness, workplace influence, and increased financial knowledge strongly encouraged interest in life insurance. Correlation analysis indicated a significant positive relationship between awareness and motivation, and a significant negative relationship between awareness and perceived barriers. Overall, the results suggest that young university professionals are receptive to life insurance. It is therefore recommended that the University of Baguio incorporate basic insurance education into institutional programs such as the ONE P Orientation and General Assembly, and that insurance providers conduct on-campus orientations to clarify policy options and address cost related misconceptions.